2012
DOI: 10.5089/9781475565829.001
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Multipliers and the State of the Economy

Abstract: Only a few empirical studies have analyzed the relationship between fiscal multipliers and the underlying state of the economy. This paper investigates this link on a country-bycountry basis for the G7 economies (excluding Italy). Our results show that fiscal multipliers differ across countries, calling for a tailored use of fiscal policy. Moreover, the position in the business cycle affects the impact of fiscal policy on output: on average, government spending, and revenue multipliers tend to be larger in dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
155
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(184 citation statements)
references
References 22 publications
15
155
0
14
Order By: Relevance
“…While there is a significant amount of empirical studies on the asymmetry of fiscal multipliers (Auerbach and Gorodnichenko, 2012 a,b;and Baum et al, 2012), the theoretical literature on the topic is scarce. One notable exception is Michaillat (2014), who finds in a search-and-matching framework that fiscal multipliers are higher in recessions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is a significant amount of empirical studies on the asymmetry of fiscal multipliers (Auerbach and Gorodnichenko, 2012 a,b;and Baum et al, 2012), the theoretical literature on the topic is scarce. One notable exception is Michaillat (2014), who finds in a search-and-matching framework that fiscal multipliers are higher in recessions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rather than relying on regime-switching models to estimate state-dependent multipliers (Auerbach and Gorodnichenko, 2012;Baum et al, 2012;and Batini et al, 2012), we use the local projection method (Jordà, 2005) as in Jordà and Taylor (2013) and Ramey and Zubairy (2013). As in Guajardo et al (2014) and Alesina et al (2013), we emphasize the distinction between tax-based and expenditure-based consolidations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, some studies have found that fiscal multipliers in advanced economies tend to be higher in downturns, and especially when the zero lower bound on the nominal interest rate binds (Christiano et al (2011)), than in expansions (see, e.g., Auerbach and Gorodnichenko (2012), Baum et al (2012), Batini et al (2012)). Differently from these papers, Owyang et al (2013) suggest that, when considering a longer time period (i.e., from 1890 to 2010), there is no strong evidence that multipliers are higher during recessions in the United States.…”
Section: Related Literature and Comparison With Our Resultsmentioning
confidence: 99%
“…Auerbach and Gorodnichenko [2012b] and Batini et al [2012] obtain similar results by looking at a larger sample of OECD countries. Baum et al [2012] adopt a non-linear threshold VAR and -more importantly for our purposes -use output gap (rather than GDP growth) to define the cycle and better identify business fluctuations (see also Harding and Pagan [2002]). They investigate six of the G7 economies from the 1970s to 2011 and find that in all cases the magnitude of the multiplier size is increasing with the negative output gap.…”
Section: The Modelmentioning
confidence: 99%